The Concept of Social Justice in Selected Novels by Hamka (Malay Literature, 2025)
Hamka, an Indonesian philosopher and writer, frequently highlighted the injustices caused by the Minangkabau people’s rigid adherence to Adat Pepatih, a set of matrilineal laws and customs, particularly in the division of inheritance. Yet most critical writings on his novels focus on their pedagogical value, mentioning little about the Islamic theological perspective embedded in his fictional representation of social injustice. This paper uses critical and qualitative content analysis of the concept of social justice or, more specifically, its lack thereof, as represented in his novels, through the Islamic philosophical framework of Syed Naquib al-Attas, who is well known for his in-depth perspective of Islamic theological concepts, including justice. Al-Attas posited that the Islamic concept of justice (adl) is the ability to put things in their proper place. According to him, this sense of justice is ingrained in every individual before they are born into this world, forming an essential part of their natural disposition (fitrah). Accordingly, the findings of this paper suggest that acts of injustice caused by the Minangkabau society’s emphasis on materialism and the belittling of love in young lovers who wish to marry, as shown in Hamka’s novels, violate this sense of justice. In conclusion, rigid adherence to Minangkabau laws and customs in Hamka’s novels can be viewed as detrimental to society and violates mankind’s natural disposition (fitrah). Full text: PDF